Brainwave motor control - Sha’abani, Mohd Nurul Al-Hafiz; Mohd Faizol, Muhammad Aminul Haikal; Zainuddin, Nazihah; Ganis, Theodolfo Albern (Penerbit UTHM, 2020)
Stroke is a brain attack. It can happen to anyone at any time. It occurs when blood flow to an area of brain is cut off. When this happens, brain cells are deprived of oxygen and begin to die. When brain cells die during stroke, abilities controlled by that area of the brain such as memory and muscle control are lost [1]. Patients who suffered stroke will become physically disabled whether on the upper body, lower body or even both. Thus, such patient needs a device to aid them to move from one place to another. The device is a wheelchair. There are many benefits of using wheelchairs such as it can help them to make a movement and to enable them to do their daily activities as usual. But for the paralyze patient, the manual wheelchair is not suitable for them. It is because, the manual wheelchair requires high level strength. Next, it needs to rely on someone to push the chair. It will cause more burdens to other people [2]. To help this disable people to solve their problem and make them easy do their daily activities as usual by building a wheelchair controlled by a brainwave.